2008
DOI: 10.1186/1471-2164-9-255
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide gene expression profiling analysis of Leishmania major and Leishmania infantum developmental stages reveals substantial differences between the two species

Abstract: BackgroundLeishmania parasites cause a diverse spectrum of diseases in humans ranging from spontaneously healing skin lesions (e.g., L. major) to life-threatening visceral diseases (e.g., L. infantum). The high conservation in gene content and genome organization between Leishmania major and Leishmania infantum contrasts their distinct pathophysiologies, suggesting that highly regulated hierarchical and temporal changes in gene expression may be involved.ResultsWe used a multispecies DNA oligonucleotide microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 78 publications
8
131
0
3
Order By: Relevance
“…For diverse groups of genes, this similarity in mRNA levels can be extended to concerted changes during differentiation or in perturbation experiments, suggesting that the transcriptome of these parasites is organized in clusters of transcripts exhibiting similar transcript abundance profiles (Ouellette & Papadopoulou, 2009; Rochette et al, 2008; Veitch et al, 2010). Also the abundance of certain ncRNAs varies between distinct forms of T. brucei (Michaeli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For diverse groups of genes, this similarity in mRNA levels can be extended to concerted changes during differentiation or in perturbation experiments, suggesting that the transcriptome of these parasites is organized in clusters of transcripts exhibiting similar transcript abundance profiles (Ouellette & Papadopoulou, 2009; Rochette et al, 2008; Veitch et al, 2010). Also the abundance of certain ncRNAs varies between distinct forms of T. brucei (Michaeli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Their approach is limited, however, to the quantification of transcript intensities whose locations have already been specificed from gene annotations or an external datasource. Rochette et al have reported a set of overlapping transcripts at a genome-wide level in the parasite Leishmania [17]. These transcripts were identified by experimental means (5 -RACE) in a genome significantly smaller than yeast, however, and do not represent a comprehensive computational approach to transcript discovery.…”
Section: Northern Analysis Of Overlapping Predictionsmentioning
confidence: 99%
“…This may be attributed to differences in stage-regulated gene-expression patterns between L. infantum and L. major (Rochette et al, 2008), but may also arise from amino-acid differences in the respective enzymes.…”
Section: Introductionmentioning
confidence: 99%